cuento en el aprendizaje de la matemática : Una propuesta abierta de investigación- acción - Fernández Bravo, José Antonio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2001)
This is an educational experience open to investigation. Its aim was to find out which tales were suitable to be used in order to learn Mathematics. A tale is proposed as a work hypothesis to play with in class. We reached definite conclusion thanks to our students’ answers according to certain methodological parameters.